2020
DOI: 10.1177/0954409720913759
|View full text |Cite
|
Sign up to set email alerts
|

New laboratory methodologies to analyse the top of rail friction modifier performance across different test scales

Abstract: Test methodologies originally developed for greases have been adapted to be used for top of rail friction modifiers (TORFMs). This has included: a small-scale benchtop tribometer to measure the tackiness of different TORFMs, attaching an applicator bar to a section of rail and rolling a scaled-wheel through the TORFM applied to the rail head to analyse the effect of different variables on pick-up, and applying TORFM to a full-scale test facility to analyse the scaling effects and the effect of slip, load and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…14,16 While these studies give possible test approaches, the application process and properties for TOR products are very different to greases, so the findings cannot be transferred. One laboratory-based study has been carried out on TOR product pick-up, 17 but in this work, friction was not measured and mechanisms of pick-up/carry-down were not explored in detail. Recently field studies carried out have shown that TOR products do not appear to be carried down more than a few hundred metres on the rail 18,19 From this work, however, indications were that the product on the wheel could be effective for >3 km.…”
Section: Introductionmentioning
confidence: 99%
“…14,16 While these studies give possible test approaches, the application process and properties for TOR products are very different to greases, so the findings cannot be transferred. One laboratory-based study has been carried out on TOR product pick-up, 17 but in this work, friction was not measured and mechanisms of pick-up/carry-down were not explored in detail. Recently field studies carried out have shown that TOR products do not appear to be carried down more than a few hundred metres on the rail 18,19 From this work, however, indications were that the product on the wheel could be effective for >3 km.…”
Section: Introductionmentioning
confidence: 99%